Der Kreis : eine Monatschrift. (Zürich : Der Kreis, 1958)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : maandelijks
Redactie : Postfach 547 Fraumünster, Zürich 22
Duits
Periodiek